Automatic Tobacco Dryer Refrigeration System Optimization Using PLC and SCADA - Syahid Syahid; Mochamad Muqorrobin; Yusnan Badruzzaman; Aggie Brenda Vernandez; Akhmad Jamaah (Politeknik Negeri Lhokseumawe, 2023)
In many cases, tobacco leaves are still dried using conventional methods, which relies merely on sunlight, thus making it difficult for farmers to dry them in the rainy season. Tobacco leaves rot easily, so alternative drying methods that are not weather dependent are required. Our research offers a solution by making a tobacco leaf drying machine with a refrigeration system. This tool can accommodate 5 kg of tobacco and can be controlled by a PLC and monitored using SCADA. The drying test was carried out at a temperature setting of 40°C–50°C and a humidity of around 25%–55%. The first test was drying 1 kg of tobacco leaves with a moisture content of 30%, which required a drying time of up to 2 hours and 40 minutes. After the drying process, the average weight of tobacco leaves became 287.8 g with a moisture content of 12%. The second test was the drying of 5 kg of tobacco leaves with a moisture content of 30%, which required a drying time of up to 4 hours and 15 minutes. After the drying process, the weight of the tobacco leaves was 880 g and the moisture content was 11.5%. The test results show that tobacco leaves can be dried without changing their original color and shape, even though they had experienced a decrease in mass and water content.